Desain Unit Pengolahan Bioetanol untuk Petani di Desa Ngajum Kecamatan Sumber Pucung Kabupaten Malang - Guritno, Bambang; Argo, Bambang Dwi; Yulianingsih, Rini (Jurnal Rekayasa Mesin, 2011)
The aim of the research is to develop bio-ethanol processing unit in small size using simple technology, which can be used by Cassava farmers in the village of Ngajum Sumber Pucung Malang. The capacity of Bioethanol processing unit provided is 100 liters/process which consists of sieve, cooker with cooling mash, fermenter, and distillation unit. Tests on several processing units give the following results: Sieve driven by 7.5 HP diesel engines. Sieve cylinder made of wood cylinder with 40 cm of diameter and 45 cm of length. Sieve has a capacity of 613 kg/h. Cooker tank made of stainless steel plate 4 mm and has dimensions 77 cm of diameter and 150 cm of height. There are 4 pieces of pipe stainless steel 6" placed at the bottom serving as heat exchanger. Cooling Mash has heat transfer surface area of 3.11 m2 that consists of 26 stainless steel pipe 1 ½" of diameter and 100 cm of length . Cooking efficiency is 38% with fuel of firewood with a moisture content of 50%. At steady state conditions, Cooling mash is capable to remove energy from substance of 280 kcal/min at mass flow rate of substance of 2.34 l/s and mass flow rate of cooling water of 0.6 l/s.Fermenter tank has made of stainless steel and has dimensions 110 cm of diameter and 240 cm of height. The mixer’s fermenter is driven by a ½ HP electric motor. To maintain the material temperature at 32 oC, the fermenter equipped with a cooling unit that is sprinkler water around the tube. Distillation unit has made of stainless steel 304 and consists of beer column, the column rectifying, pre-heater, condensers and equipped with boiler.Keywords : Performance, Bioethanol Processing Unit, Small Scale.